Radiation hardness and timing performance in MALTA monolithic pixel sensors in TowerJazz 180 nm. (1st April 2022) - van Rijnbach, M.; Allport, P.; Asensi, I.; Berdalovic, I.; Bortoletto, D.; Buttar, C.; Cardella, R.; Dachs, F.; Dao, V.; Denizli, H.; Dobrijevic, D.; Dyndal, M.; et al.
Abstract: The MALTA family of depleted monolithic pixel sensors produced in TowerJazz 180 nm CMOS technology target radiation hard applications for the HL-LHC and beyond. Several process modifications and front-end improvements have resulted in radiation hardness >10 15 1 MeV neq /cm 2 and time resolution below 2 ns, with uniform charge collection and efficiency across the pixel of size 36.4 × 36.4 µm 2 with small collection electrode. This contribution will present the comparison of samples produced on high-resistivity epitaxial silicon with Czochralski substrates, before and after neutron irradiation, and results from MALTA2 with a new cascoded front-end flavour that further reduces the RTS noise.